2016
DOI: 10.4236/ojinm.2016.62002
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Sensor for the Solar Battery Guidance on the Sun Based on GeS:Sb Layered Crystals

Abstract: Photovoltaic tracking sensor monitoring the position of the sun in the sky was developed on the basis of GeS:Sb layered crystals. The operating principle of this sensor is based on the phenomenon of photovoltaic effect in GeS:Sb crystals; the magnitude and sign of generated photo-emf depend on the position of the light probe relative to the ohmic contacts, deposited on (001) surface of the crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…41 Since then, theoretical calculations of orthorhombic GeS have also indicated the presence of Ge 4s states at the VBM, but other studies of GeS are limited to monolayers and amorphous materials, the electronic structures of which differ significantly from the electronic structures of bulk crystals. [42][43][44][45] Theoretical calculations on orthorhombic GeSe have also suggested that the Ge 4s orbitals contribute to the VBM, with one study loosely comparing the calculated density of states to XPS measurements of the valence band spectra. 20,46,47 GeS and GeSe are known to adopt distorted crystal structures, 48 and theoretical studies on both have demonstrated the asymmetric electron densities expected in materials with stereochemically active lone pairs.…”
Section: Ge Lone Pair Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Since then, theoretical calculations of orthorhombic GeS have also indicated the presence of Ge 4s states at the VBM, but other studies of GeS are limited to monolayers and amorphous materials, the electronic structures of which differ significantly from the electronic structures of bulk crystals. [42][43][44][45] Theoretical calculations on orthorhombic GeSe have also suggested that the Ge 4s orbitals contribute to the VBM, with one study loosely comparing the calculated density of states to XPS measurements of the valence band spectra. 20,46,47 GeS and GeSe are known to adopt distorted crystal structures, 48 and theoretical studies on both have demonstrated the asymmetric electron densities expected in materials with stereochemically active lone pairs.…”
Section: Ge Lone Pair Literature Reviewmentioning
confidence: 99%
“…20,46,47 GeS and GeSe are known to adopt distorted crystal structures, 48 and theoretical studies on both have demonstrated the asymmetric electron densities expected in materials with stereochemically active lone pairs. 42,45,49 However, neither material has been studied using HAXPES, and this would be the most effective method for confirming (or otherwise) the presence of Ge 4s states at the VBM. Beyond the germanium chalcogenides, studies of Ge 4s lone pairs remain limited.…”
Section: Ge Lone Pair Literature Reviewmentioning
confidence: 99%